2016
DOI: 10.1089/tmj.2016.0045
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Foundations of Telemedicine Interventions in Primary Care

Abstract: Telemedicine has significant potential to address many of the challenges facing primary care in today's healthcare environment. Challenges still remain in validating its impact on clinical outcomes with scientific rigor, as well as in standardizing methods to assess cost, but patient and provider acceptance is increasingly making telemedicine a viable and integral component of primary care around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
188
0
29

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(219 citation statements)
references
References 111 publications
(120 reference statements)
2
188
0
29
Order By: Relevance
“…In the context of modern disease management programs, default values or values defined by a case manager are assigned as a threshold for the collected parameters to trigger an alert when significant deterioration in patient status occurs. 25 This approach has several major limitations. First, limited evidence exists for optimal threshold identification; thresholds may differ between patients and may change during the course of a chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of modern disease management programs, default values or values defined by a case manager are assigned as a threshold for the collected parameters to trigger an alert when significant deterioration in patient status occurs. 25 This approach has several major limitations. First, limited evidence exists for optimal threshold identification; thresholds may differ between patients and may change during the course of a chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A systematic review investigating the merits of telehealth interventions in primary care found that telehealth was generally more acceptable to patients than providers, outcomes were at least as effective as in-office care, and costs were no higher than for in-office care. 10 Improvements, however, are still needed. A recent study by Teladoc, Inc., an independent company offering mobile device-based and Internetbased medical care delivered by a physician who does not have an established relationship with the patient, found that users were not preferentially located in underserved communities, and providers had poorer performance than physician office visits on measures such as ordering diagnostic testing and prescribing appropriate antibiotics for bronchitis.…”
mentioning
confidence: 99%
“…This stepwise approach is significantly correlated with the degree of mobile health adoption by providers, and thus availability to patients . The transition of this technological advancement to the primary‐care arena has yet to be properly facilitated within the healthcare reimbursement structure, which may be the most significant barrier to widespread utilization of mHealth within the current framework …”
Section: Mhealth Technology Interpretation and Adoption By Cliniciansmentioning
confidence: 99%